Land Policy Reconstruction from the Notary Authority Perspective: Optimization Efforts for Electronic Land Registration System - Intan Hanisa; I Gusti Ketut Ayu Rachmi Handayani; Lego Karjoko (Greenation Research & Yayasan Global Resarch National, 2024)
This research examines the urgency of reconstructing land policy in the context of digital transformation of the land registration system, focusing on the expansion of notary authority. Using a normative juridical research method with conceptual and statutory approaches, this study analyzes the transformation from conventional to electronic land registration systems. The results indicate that optimizing the electronic land registration system requires three main pillars: adequate technological infrastructure, a comprehensive legal framework, and human resource capacity development. The implementation of electronic systems has proven to increase time efficiency by 60% and reduce operational costs by 40%. The role of notaries has undergone significant expansion, including authority for electronic document verification and digital signature validation. The optimization model developed includes land database integration, digital verification systems, and artificial intelligence-based monitoring mechanisms. The implications of this research provide theoretical and practical foundations for land policy reform that is adaptive to digital technology developments.